The Influence of Profitability on Share Prices of Food and Beverage Sub-Sector Companies Listed on the Indonesian Stock Exchange in 2019 - Marnilin, Feni (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
Investors need to know information about the company's shares, therefore relevant information is needed in making investment decisions. The value of the stock price can be predicted by the performance generated by the company. This study aims to determine the effect of profitability as measured by Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS) on Stock Prices in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2019 partially and simultaneously. The sample used in this study used purposive sampling method, namely the annual financial statements of the Food and Beverage Sub-Sector Companies on the IDX in 2019 as many as 27 companies. The results of this study indicate that partially Return on Assets (ROA) has a significant effect on Stock Price, Return on Equity (ROE) has a significant effect on Stock Price, and Earning per Share (EPS) has a significant effect on Stock Price. While simultaneously Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS) have a significant effect on Stock Prices. Keyword : Return on Assets (ROA), Return on Equity (ROE),Earning per Share (EPS), Stock Prices